2013 IEEE Symposium on Computational Intelligence for Engineering Solutions (CIES) 2013
DOI: 10.1109/cies.2013.6611723
|View full text |Cite
|
Sign up to set email alerts
|

Interactive particle swarm optimization for the architectural design of truss structures

Abstract: This paper presents an interactive framework for the design of truss structures with aesthetic criteria. The truss chords are described using NURBS, a tool widely used in computer aided design (CAD) programs to describe free-form geometry. This allows for a convenient interface between the optimization scheme, a particle swarm optimizer, and the user. Driven from the fact that aesthetic design goals are not easily quantifiable, key elements are introduced and implemented herein towards an interactive framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For structural analysis purposes a finite element package, such as ANSYS, could be coupled to MATLAB serving as the numerical analysis tool as the authors have demonstrated before [49]. The idea behind selecting such a tool, which comes with a strong finite element (FE) solver, is to later expand this semi-automated design framework on surface and 3D structures.…”
Section: Pso For Structural Optimization With Constraintsmentioning
confidence: 98%
See 3 more Smart Citations
“…For structural analysis purposes a finite element package, such as ANSYS, could be coupled to MATLAB serving as the numerical analysis tool as the authors have demonstrated before [49]. The idea behind selecting such a tool, which comes with a strong finite element (FE) solver, is to later expand this semi-automated design framework on surface and 3D structures.…”
Section: Pso For Structural Optimization With Constraintsmentioning
confidence: 98%
“…In previous works, the efficacy of the PSO was validated on a finite element implementation for the well-known 10-bar truss benchmark problem [3,49]. This section presents the design of a 2D horizontal truss without user interaction, i.e., for purely structural optimization, in order to demonstrate the advantages of the NURBS parametrization.…”
Section: Implementation Of the Proposed Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Grasshopper ® , a free parametric design plugin for the popular three-dimensional modeling application Rhinoceros ® , includes an easy-to-use evolutionary solver named Galapagos (Rutten, 2013). Simulated annealing (also implemented in Galapagos) and particle swarm optimization are other metaheuristics that are sometimes used in the architectural field (e.g., Luebkeman & Shea, 2005; Felkner et al, 2013). According to Yang (2010), metaheuristics are also widespread in engineering design.…”
Section: Introductionmentioning
confidence: 99%